2010
DOI: 10.1038/nbt.1636
|View full text |Cite
|
Sign up to set email alerts
|

Live attenuated influenza virus vaccines by computer-aided rational design

Abstract: Influenza claims 250,000 - 500,000 lives annually worldwide. Despite existing vaccines and enormous efforts in biomedical research, these staggering numbers have not changed significantly over the last two decades1, motivating the search for new, more effective, vaccines that can be rapidly designed and easily produced. Using influenza virus strain A/PR/8/34, we describe a systematic, rational approach, termed Synthetic Attenuated Virus Engineering (SAVE), to develop new, efficacious live attenuated influenza … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
277
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 250 publications
(297 citation statements)
references
References 24 publications
17
277
1
2
Order By: Relevance
“…As discussed earlier, codon pair de-optimization has been used to synthesize novel viral vaccine candidates, validating that codon pair bias influences translational efficiency (Coleman et al 2008;Mueller et al 2010). Similarly, Moura et al considered 72 orthologous highly conserved genes from the three domains of life and showed that synonymous mutations were selected to maintain codon context biases (Moura et al 2011).…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 97%
See 1 more Smart Citation
“…As discussed earlier, codon pair de-optimization has been used to synthesize novel viral vaccine candidates, validating that codon pair bias influences translational efficiency (Coleman et al 2008;Mueller et al 2010). Similarly, Moura et al considered 72 orthologous highly conserved genes from the three domains of life and showed that synonymous mutations were selected to maintain codon context biases (Moura et al 2011).…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 97%
“…The approach, termed synthetic attenuated virus engineering (SAVE) has also been applied to influenza virus (Mueller et al 2010) and respiratory syncytial virus (Meng et al 2014).…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%
“…We have been designing genes and viruses containing hundreds of unfavorable codon pairs, a process we call synthetic attenuated virus engineering. Recoded viral genomes are typically attenuated but strongly immunogenic in animals (16,22,23).…”
mentioning
confidence: 99%
“…In May 2010, Venter's group announced the first synthetic life form, a feat requiring synthesizing a 1.08 megabase bacterial chromosome [8]. The advent of cheap synthesis will have many exciting new applications throughout the life sciences (including our own work on synthetic vaccines [5,16,15]): the freedom to design new sequences to specification leads to a variety of new algorithmic problems on sequences.…”
Section: Introductionmentioning
confidence: 99%